2019
DOI: 10.1186/s13058-019-1114-3
|View full text |Cite
|
Sign up to set email alerts
|

CXCL17-derived CD11b+Gr-1+ myeloid-derived suppressor cells contribute to lung metastasis of breast cancer through platelet-derived growth factor-BB

Abstract: BackgroundMetastasis is the major cause of death from breast cancer. Colonization and adaption of metastatic cells in distant organs is a rate-limiting step of the cancer spreading. The underlying mechanisms responsible for the colonization of breast cancer to lung metastatic niches are not fully understood.MethodsSpecific gene contributions to lung metastasis were identified by comparing gene profiles of 4T1 tumors metastasizing to various organs via microarray. The oncogenic properties CXCL17 were examined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 47 publications
0
61
0
Order By: Relevance
“…These factors are hailed as alternative vasculature-creating mechanisms, but equally effective and perhaps overlapping, since they use similar signaling pathways (extracellular-related kinase (ERK)/Akt or mitogen-activated protein kinase (MAPK)), while the tumor-activated pSTAT3 pathway in MDSCs results in their generation [58,64]. Kuo et al detected that CXCL17 supported de novo angiogenesis and lung metastasis by means of PDGF expressing CD11b + Gr-1 + MDSC in mice [70].…”
Section: Secondary Angiogenic Mechanismsmentioning
confidence: 99%
“…These factors are hailed as alternative vasculature-creating mechanisms, but equally effective and perhaps overlapping, since they use similar signaling pathways (extracellular-related kinase (ERK)/Akt or mitogen-activated protein kinase (MAPK)), while the tumor-activated pSTAT3 pathway in MDSCs results in their generation [58,64]. Kuo et al detected that CXCL17 supported de novo angiogenesis and lung metastasis by means of PDGF expressing CD11b + Gr-1 + MDSC in mice [70].…”
Section: Secondary Angiogenic Mechanismsmentioning
confidence: 99%
“…In colorectal cancer mouse model, instead, high amounts of CXCL1 released by TAMs have been reported to attract CXCR2expressing MDSCs to generate liver pMNs (157). Other studies reported additional chemokines promoting MDSC transport to pMNs, such as MCP-1 (monocyte chemoattractant protein 1) (158), CCL12 (159), CCL9 (160), CCL15 (161), and CXCL17 (162), although the source of these cytokines in pMNs remains often unclear. Nowadays there are accumulating evidences that pro-metastatic molecules can be transported not only as soluble factors, but also inside tumor-derived microvesicles such as TEXs (13,163,164).…”
Section: Mdscs Role On Generating Pre-metastatic Nichementioning
confidence: 99%
“…MDSCs play a critical role on initiating and sustaining the development of a new vascularization in pMN, primarily by secreting a variety of regulatory molecules such as VEGFA (173). Recently, Hsu et al demonstrated that high amount of platelet-derived growth factor BB (PDGF-BB) released by pMN-infiltrating MDSCs increases angiogenesis and chaperone tumor cells through the bloodstream to new sites of metastasis (162). Another MDSC-associated proangiogenic factor is Bv8, which is released by a STAT3-dependent pathway (174,175).…”
Section: Mdscs Role On Generating Pre-metastatic Nichementioning
confidence: 99%
“…More recently, focus has shifted towards the ligand. PDGFB is dramatically induced by TGFβ in normal mammary epithelial cells (10), and in the past year, was revealed to promote cancer associated fibroblast (CAF) invasiveness and lung metastasis in the murine mammary 4T1 tumor model (11)(12)(13). Overall, these findings led to our current study testing how PDGFRβ signaling alters BC initiation, progression, and/or metastasis.…”
mentioning
confidence: 92%